2010
DOI: 10.1371/journal.pone.0013840
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Serum/Glucocorticoid Regulated Kinase 1 in Colorectal Tumours Is Largely Independent of Promoter Hypermethylation

Abstract: BackgroundWe have previously shown that serum/glucocorticoid regulated kinase 1 (SGK1) is down-regulated in colorectal cancers (CRC) with respect to normal tissue. As hyper-methylation of promoter regions is a well-known mechanism of gene silencing in cancer, we tested whether the SGK1 promoter region was methylated in colonic tumour samples.Methodology/Principal FindingsWe investigated the methylation profile of the two CpG islands present in the promoter region of SGK1 in a panel of 5 colorectal cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In terms of regulation of SGK1 expression, in CRC, mutations in SGK1 may be observed in up to 2% of cases, although the mutations are usually missense and not isolated to the kinase domain [38]. Our previous work has identified that down-regulation in CRCs appears to be independent of promoter hypermethylation [39] and these observations suggest that control is likely to be transcriptionally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of regulation of SGK1 expression, in CRC, mutations in SGK1 may be observed in up to 2% of cases, although the mutations are usually missense and not isolated to the kinase domain [38]. Our previous work has identified that down-regulation in CRCs appears to be independent of promoter hypermethylation [39] and these observations suggest that control is likely to be transcriptionally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, high SGK1 expression has been implicated in cell survival in different neoplasias (7, 8, 1214). However, the role of SGK1 in cancer cells may be rather complex and largely dependent on the cellular context, because in some cancers SGK1 expression is down-regulated (8, 15, 16). The negative predictive role of low SGK1 expression in ACC in our study was robust and remained evident also after adjustment for multiple prognostic factors including GC secretion and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…prostate, hepatocellular, and colorectal cancer) (8, 15, 16). The impact of SGK1 expression on clinical outcome has been evaluated only in a small number of studies, again with contradictory results in different cancers (14, 17).…”
mentioning
confidence: 99%
“…In solid tumors, SGK1 is often upregulated in most of the cancer, such as adrenocortical adenomas ( 26 ), breast cancer ( 14 ), endometrial cancer ( 30 ), gastric cancer (GC) ( 15 ), lung cancer ( 16 , 17 , 31 ), medulloblastoma ( 32 ), oral squamous cell carcinoma (OSCC) ( 33 ), ovarian cancer ( 34 ), prostate carcinoma ( 20 , 35 ), renal clear cell carcinoma ( 32 ), and rhabdomyosarcoma ( 36 ). Although the exact reason why SGK1 expression in cancer in the intestinal system is downregulated remains unclear ( 24 , 25 ), it has been postulated to most likely be due to transcriptional repressors acting on the SGK1 promoter ( 37 ). What these repressors are and how they are controlled remains unclear ( 37 ).…”
Section: Clinical Value Of Sgk1 In Cancermentioning
confidence: 99%